Application of Digital Image Correlation (DIC) in resonance machines for measuring fatigue crack growth - P. Lorenzino; G. Beretta; A. Navarro (Fracture and Structural Integrity)
This paper presents a simple experimental procedure that greatly facilitates the use of digital image correlation (DIC) techniques in fatigue test conducted in resonant testing machines, without the need of test interruptions. This is possible due to the implementation of USB interface optical microscopes of very small dimensions, so that they can be mounted on the specimen as a contact extensometer. Thus, the microscopesample assembly oscillates at the resonance frequency of the test. This is how, although the resonant testing machine is in motion, and although the specimen is subjected to fatigue, changing its dimensions according to the applied load, the acquired image is completely static. This allows the evaluation of the plastic deformations generated by the crack growth, avoiding the elastic ones. Preliminary results on monitoring cracks with this technique on flat specimens with cylindrical notches of 1050 aluminium alloy are also presented.